Combination of Fluorescence-Guided Surgery With Photodynamic Therapy for the Treatment of Cancer - Jun He MD; Leping Yang MD; Wenjun Yi MD; Wentao Fan MD; Yu Wen MD; Xiongying Miao MD; Li Xiong MD (Molecular Imaging)
Specific visualization of body parts is needed during surgery. Fluorescence-guided surgery (FGS) uses a fluorescence contrast agent for in vivo tumor imaging to detect and identify both malignant and normal tissues. There are several advantages and clinical benefits of FGS over other conventional medical imaging modalities, such as its safety, effectiveness, and suitability for real-time imaging in the operating room. Recent advancements in contrast agents and intraoperative fluorescence imaging devices have led to a greater potential for intraoperative fluorescence imaging in clinical applications. Photodynamic therapy (PDT) is an alternative modality to treat tumors, which uses a light-sensitive drug (photosensitizers) and special light to destroy the targeted tissues. In this review, we discuss the fluorescent contrast agents, some newly developed imaging devices, and the successful clinical application of FGS. Additionally, we present the combined strategy of FGS with PDT to further improve the therapeutic effect for patients with cancer. Taken together, this review provides a unique perspective and summarization of FGS.